2010
DOI: 10.1111/j.1745-4514.2009.00281.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF THERMAL TREATMENT ON PHENOLIC COMPOUNDS AND FUNCTIONALITY LINKED TO TYPE 2 DIABETES AND HYPERTENSION MANAGEMENT OF PERUVIAN AND BRAZILIAN BEAN CULTIVARS (PHASEOLUS VULGARISL.) USINGIN VITROMETHODS

Abstract: The effect of thermal treatment on phenolic compounds and type 2 diabetes functionality linked to α‐glucosidase and α‐amylase inhibition and hypertension relevant angiotensin I‐converting enzyme (ACE) inhibition were investigated in selected bean (Phaseolus vulgaris L.) cultivars from Peru and Brazil using in vitro models. Thermal processing by autoclaving decreased the total phenolic content in all cultivars, whereas the 1,1‐diphenyl‐2‐picrylhydrazyl radical scavenging activity‐linked antioxidant activity inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 53 publications
3
21
1
1
Order By: Relevance
“…On the one hand, heat treatment had a decomposition effect on phenolic compounds (Ranilla et al, 2010), which also may have been lost to the solution, in which the bamboo shoots were boiled; on the other hand, heat treatment could make the existed polyphenol oxidases inactive so that prevented polyphenols' decomposition (Yamaguchi et al, 2003), and heat treatment could promote dietary fiber-binding type polyphenols decomposition into free phenolic compounds and then made the detected value much higher (Stewart et al, 2000). In contrast with fresh bamboo shoots, the antioxidant capacity of boiled samples reduced apparently, steamed ones remained unchanged, and stirfried ones increased slightly (Fig.…”
Section: Effects Of Cooking Methods On Total Phenolic Content and Totmentioning
confidence: 99%
“…On the one hand, heat treatment had a decomposition effect on phenolic compounds (Ranilla et al, 2010), which also may have been lost to the solution, in which the bamboo shoots were boiled; on the other hand, heat treatment could make the existed polyphenol oxidases inactive so that prevented polyphenols' decomposition (Yamaguchi et al, 2003), and heat treatment could promote dietary fiber-binding type polyphenols decomposition into free phenolic compounds and then made the detected value much higher (Stewart et al, 2000). In contrast with fresh bamboo shoots, the antioxidant capacity of boiled samples reduced apparently, steamed ones remained unchanged, and stirfried ones increased slightly (Fig.…”
Section: Effects Of Cooking Methods On Total Phenolic Content and Totmentioning
confidence: 99%
“…Many studies showed their beneficial effects on blood cholesterol, glucose and insulin levels, in addition to prevention of various cancers, such as gastrointestinal, breast and prostate. These properties have been attributed to the unique nutritional composition of the bean that is rich in fibre and phenolic compounds, and low in total fat and saturated fat (Boateng et al, 2008;Karababa, 2006;Marathe et al, 2011;Ranilla et al, 2010;Sievenpiper et al, 2009;Thompson et al, 2008;Wu et al, 2004;Xu & Chang, 2009). The Chinese and Brazilian beans have a similarly high content of dietary fibre (Wu et al, 2004;Costa et al, 2006).…”
Section: Nutritional Qualitymentioning
confidence: 99%
“…The beneficial effects of polyphenols on human health are expressed primarily through the reduction of the oxidative stress [4]. Some polyphenols are also able to exert antiapoptotic, antiaging, as well as anticarcinogenic activity, overall inhibiting the cell proliferation processes [5, 6].…”
Section: Introductionmentioning
confidence: 99%